Behaviorism at twenty-five - Roback, A. A. (Abraham Aaron), 1890-1965 (Cambridge, Mass. : Sci-Art Publishers, 1937)
"It is about fifteen years now since my Behaviorism and Psychology appeared; and although an enlarged edition was to be published shortly thereafter in the International Library of Psychology under the title of The Behaviorist Movement, I thought it would be wiser to see what progress the Movement was making in the next decade before elaborating on the first book. It was not long before I could sense that the Movement was petering out, although the literature on it was growing (compare the first few months of the Technocracy craze) and it had occurred to me that in order to do full justice to all phases of behaviorism, a volume of about 700 pages would be necessary, while on the other hand, behaviorism was not worth the pains of such a time-consuming labor and financial responsibility. This year, however, marks the twenty-fifth anniversary of behaviorism. It is strange that the event had not been celebrated in objectivist circles, and that it was left to an anti-behaviorist to observe the occasion. I had then decided to honor behaviorism on my own account, and bring out a little book, containing not only added material but a full bibliography of the writings on the subject since 1923, when my Behaviorism and Psychology appeared."--Preface. (PsycINFO Database Record (c) 2012 APA, all rights reserved).
Keywords: Behaviorism (Psychology).; Behaviorism (Psychology).; Behaviorism